Fundamental Questions of Administrative and Criminal Investigations for the Protection of the Financial Interests of the EU - Farkas, Ákos (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
One of the most meaningful results of the past decades in the EU is forming a new criminal law cooperation system which is building on a new paradigm of operational cooperation between EU MSs. The new system pushed back to the background of the traditional, legal aid-based system. One of the characteristics of this is tighter cooperation in the investigation of both administrative and criminal. This contribution concentrates on presenting the features of this topic.KEYWORDS: the administrative investigation, criminal investigation, protection of the financial interests of the EU, OLAF, Eurojust, EPPO